Crypto-watermarking of images for secure transmission over cloud. Issue 1 (2nd January 2020) - Kaur, Gurpreet; Agarwal, Rekha; Patidar, Vinod
Abstract: With ever increasing usage of Cloud based data storage in various domains, the security and authentication of such data is a matter of concern for the end user. Data centres being the third party servers are always prone to data leakage. Moreover investigating an illegal activity over cloud is not possible. The proposed scheme provides a solution to the highly confidential medical data(image) of patients to be shared with authentic users (hospital staff) over the cloud. This work proposes a collective blind crypto-watermarking scheme that provides not only security but also authentication and ownership protection to the medical information of the patients. The scheme is based on a bit level extraction and embedding of watermark in spatial domain. A chaotic mapping based substitution initially obfuscates the host image then a watermark image is embedded into the host image. At next stage the watermarked image is encrypted in fractional Hartley transform domain. This crypto-watermarked image is shared over vulnerable cloud storage. The chaotic parameters and the transform orders serve as the secret keys. The results and analysis indicate that proposed scheme is secure against potential attacks and provides a solution to the security risks associated with the cloud based data storage services.